Overview of River Hydrological Issues in Kakarbhitta-Pathlaiya Road Segment of East-West Highway of Nepal - Regmi, Ram Krishna (Journal of Advanced College of Engineering and Management, 2022)
The East-West Highway of Nepal is the main trade and physical mobility corridor and of a two-lane bituminous road. Therefore, the Government of Nepal (GoN) is planning to improve it to a standard four-lane highway. In the first phase, the Government of Nepal is planning to upgrade the Kakarbhitta-Pathlaiya road which is the segment of the East-West Highway. It is vital to examine the river hydrology accurately for the appropriate location and design of the structures associated with it. This study aims to work out the features of flood and sediment of the major rivers intersecting the Kakarbhitta-Pathlaiya road. A review of the previous studies and field observation via a walk-through survey was conducted to assess the hydrological issues. The road segment passes through the Terai. The study revealed that the issues of flooding and inundation within the Terai are more critical, and the rivers crossing the road segment transport significant amounts of sediment as well. In the stages of planning and design of the road segment, the capacity of the rivers must be enhanced for transporting water and sediment in the places of bridges. Besides, watershed management techniques and integrated water resources management approaches should be intervened.